Efeito do estrógeno na palatabilidade ao sódio de ratas com apetite ao sódio - Pereira Junior, Emilson Donizete (2018)
Excessive salt intake has been associated with the development or worsening of chronic diseases such as hypertension. Spontaneously hypertensive rats (SHR) have a typical increased sodium preference. Estrogen influences arterial pressure and sodium appetite, but we do not know how much ovarian hormones influence sodium palatability, particularly in SHR. Here we evaluated the influence of ovarian hormones on sodium palatability of female SHR. Bilateral ovariectomy (OVX) increased 0.3 M NaCl intake induced by water deprivation - partial dehydration (WD-PR) in the sodium appetite test in normotensive (Holtzman-HTZ) and adult SHR rats, compared to the respective controls (sham surgery). In the taste reactivity test, there was also an increase in the frequency of hedonic responses to intra-oral infusion of 0.3 M NaCl (IO-NaCl) in both ovariectomized normotensive and hypertensive rats. The frequency of aversive responses was not altered by ovariectomy. High-dose estrogen ( 50 μg / rat) supplementation in intact SHR (8-9 months) decreased the frequency of hedonic responses to I0-NaCl and increased frequency of aversive responses after partial rehydration before access to sodium. Estrogen supplementation also decreased 0.3 M NaCl intake without changes in frequency of hedonic or aversive responses to I0-NaCl after sodium intake. Daily replacement of estrogen (10 μg / rat) in SHR OVX decreased WD-PR-induced 0.3 M NaCl intake without changes in baseline cardiovascular parameters. This estrogen treatment reduced ANG II pressor response when compared to the same stimulus in ovariectomized rats treated with vehicle. Daily estrogen replacement (10 μg/day) also decreased the number of hedonic responses to IO-0.3 M NaCl in hypertensive rats with WD-PR- induced sodium appetite, without changes in number of aversive responses. Blockade of ANG II AT1 receptors decreased WD-PR- induced 0.3 M NaCl intake and palatability in SHR rats. In summary, the absence of ovarian hormones increased hedonic properties of the taste produced by the IO-0.3 M NaCl in rats, hypertensive and normotensive, whereas estrogen replacement and supplementation had an inhibitory effect on appetite and palatability to sodium, respectively in females SHR. The results suggest that estrogen has an inhibitory effect on sodium palatability in SHR rats, thus influencing the ingestion of this ion in these animals.